Harnessing Plasmon-Induced Hot Carriers at the Interfaces With Ferroelectrics - Kumar, Vineet; O'Donnell, Shaun C.; Sang, Daniel L.; Maggard, Paul A.; Wang, Gufeng (Frontiers in Chemistry, 2019)
This article reviews the scientific understanding and progress of interfacing plasmonic particles with ferroelectrics in order to facilitate the absorption of low-energy photons and their conversion to chemical fuels. The fundamental principles of hot carrier generation and charge injection are described for semiconductors interfaced with metallic nanoparticles and immersed in aqueous solutions, forming a synergistic juncture between the growing fields of plasmonically-driven photochemistry and semiconductor photocatalysis. The underlying mechanistic advantages of a metal-ferroelectric versus metal-nonferroelectric interfaces are presented with respect to achieving a more optimal and efficient control over the Schottky barrier height and charge separation. Notable recent examples of using ferroelectric-interfaced plasmonic particles have demonstrated their roles in yielding significantly enhanced photocurrents as well as in the photon-driven production of molecular hydrogen. Notably, plasmonically-driven photocatalysis has been shown to occur for photon wavelengths in the infrared range, which is at lower energies than typically possible for conventional semiconductor photocatalysts. Recent results thus demonstrate that integrated ferroelectric-plasmonic systems represent a potentially transformative concept for use in the field of solar energy conversion.